Perancangan Jaringan Virtual Local Area Network Menggunakan Cisco Packet Tracer Pada SMK Islam Assa’adatul Abadiyah - Noviriandini, Astrid; Bachtiar, Denny; Indriyani, Luthfi (JUKI : Jurnal Komputer dan Informatika, 2023)
Computer network is a relationship between two or more separate computer systems, through a communication medium to carry out data communication with one another in order to share resources. SMK Islamic Assa’adatul Abadiyah was founded in 1984, which stands on a land area of 1237 m2, which has three majors namely: Office Administration, Accounting, Commerce. However, in 2011 SMK Islamic Assa’adatul Abadiyah added a competency competency department, namely the competency competency in Computer and Network Engineering. Internet network is one of the human needs to date. So many human activities have become easier with the internet network. However, problems arise on a network that is not working properly, making information and communication managers less optimal in the process of sending data and teaching/learning processes in the school lab. The solution provided to deal with problems on a network that is less than optimal is to design a VLAN (Virtual Local Area Network) network and change a HUB component to a Switch as network integration, install premium antivirus on computers, allow users to access the network without any problems and security on computers are safer.